2021
DOI: 10.1001/jamanetworkopen.2021.41508
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain in Women With Obesity and Consideration of Infant Morbidity and Mortality in Clinical Practice

Abstract: prompt a review of their overall medical condition and their diet and physical activity to ensure that they are optimal, in addition to monitoring fetal growth, fetal health during labor, and the neonate after delivery, as presently practiced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some recent studies have suggested that women with pre‐pregnancy obesity should be encouraged to gain less weight than the current IOM guidelines recommend, and others have argued that no weight gain, or even some weight loss, is optimal [38]. Overall, our findings demonstrate that, among this Pacific Islander cohort, a rate of GWG below the guidelines is associated with increased risk of PTB, including among women with pre‐pregnancy obesity (excluding pre‐pregnancy obesity class III), which replicates findings of a recent multiethnic meta‐analysis [12] and is indirectly supported by studies for other perinatal outcomes among women with pre‐pregnancy obesity [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have suggested that women with pre‐pregnancy obesity should be encouraged to gain less weight than the current IOM guidelines recommend, and others have argued that no weight gain, or even some weight loss, is optimal [38]. Overall, our findings demonstrate that, among this Pacific Islander cohort, a rate of GWG below the guidelines is associated with increased risk of PTB, including among women with pre‐pregnancy obesity (excluding pre‐pregnancy obesity class III), which replicates findings of a recent multiethnic meta‐analysis [12] and is indirectly supported by studies for other perinatal outcomes among women with pre‐pregnancy obesity [39, 40].…”
Section: Discussionmentioning
confidence: 99%